Waldenstrom Macroglobulinemia Complicated with Hyperviscosity Syndrome - Jigjidkhorol, Narangerel; Batsukh, Khishigjargal; Norov, Oyundelger; Sukhbaatar, Myadagsuren; Ayurzana, Nansalmaa; Ravzanaadii, Mend-Amar; Tungalag, Saruul; Boldbaatar, Altanshagai; Purevdorj, Khulan; Jav, Sarantuya (Central Asian Journal of Medical Sciences, 2015)
Objectives: Waldenstrom Macroglobulinemia (WM) is a malignant disease of the B lymphocytes. We report on a patient in Mongolia having WM complicated with hyperviscosity syndrome. Methods: A 28 year-old Mongolian woman had symptoms due to hyperviscosity syndrome such as vision loss, headache, dizziness and, epistaxis. Upon examination, her morphology, biochemistry, histology, flow cytometry and serum protein electrophoresis indicated WM complicated with hyperviscosity syndrome. Results: The patient was was successfully treated with a combination chemotherapy and plasmapheresis. Conclusion: Hyperviscosity syndrome manifestations should be treated with plasmapheresis.